2023
DOI: 10.1021/acs.jafc.2c07239
|View full text |Cite
|
Sign up to set email alerts
|

Eucommia Bark/Leaf Extract Improves Lipid Metabolism Disorders by Affecting Intestinal Microbiota and Microbiome–Host Interaction in HFD Mice

Abstract: Eucommia bark contains many bioactive compounds and has anti-hyperlipidemic effects. However, due to the slow growth rate of the plant, there is a limited supply of this resource. Studies have demonstrated that Eucommia leaves contain active ingredients similar to those of Eucommia bark and also have anti-hyperlipidemic effects. It is not currently clear whether Eucommia leaf can be used as a substitute for Eucommia bark. Furthermore, their mechanism of action for anti-hyperlipidemia by improving the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…ELE has been widely reported to have a lipid-lowering function [ 18 , 19 , 79 , 80 ]. Our previous work also showed that ELE could reduce fat deposition on the back of finishing pigs [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…ELE has been widely reported to have a lipid-lowering function [ 18 , 19 , 79 , 80 ]. Our previous work also showed that ELE could reduce fat deposition on the back of finishing pigs [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary laboratory studies have shown that EBE and ELE contain eight identical bioactive ingredients, and fecal bacteria suspensions containing EBE and ELE signi cantly improved HFD-induced lipid metabolism disorders and elevated blood glucose levels 34 . The results showed that EBE and ELE contained similar active ingredients and signi cantly alleviated lipid metabolism disorders and blood glucose levels in the HFD-induced hyperlipidemia model 35 .…”
Section: Introductionmentioning
confidence: 92%
“…Eucommia, isolated from the dry roots of Eucommia ulmoides Oliv., is a Chinese medicine and food homolog that has antiosteoporotic, anti-inflammatory, hypoglycemic and hypolipidemic effects. Recent studies have indicated that Eucommia leaves have similar active ingredients and antihyperlipidemic effects as Eucommia bark and can modulate the gut microbiota to alleviate lipid metabolism disorders ( Wang et al., 2023a ; Wang et al., 2023b ). Eucommia leaf extract supplementation increased the relative abundance of Ruminococcaceae to promote the production of butyric acid, which upregulated the expression of GPR43 to reduce the area of adipocytes and lipid accumulation.…”
Section: Plant Natural Products Ameliorate Mafld By Regulating the Gu...mentioning
confidence: 99%